Penggambaran Hari Kiamat dengan Uslub Isti’arah (Metafora) dalam Alquran: Telaah Tafsir Al-Munir - Imroatul Azizah; Ibnu Samsul Huda (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: The verse depicting the Day of Judgment uses a lot of comparative language styles, one of which is uslub isti'arah (metaphorical style). This study aims to find verses describing the Day of Judgment with uslub isti'arah in the Qur'an. The research was conducted by analyzing the elements, types, and meanings of uslub isti'arah in the verse. The research design is descriptive qualitative with meaning analysis methods and literature review. Al-Munir's interpretation is used as the main reference in determining the meaning. The results showed that there were 144 verses with two patterns, namely 97 verses mentioning another name for the Day of Judgment according to its occurrence using the word "al-yaum” and 47 verses describing the Day of Judgment in general/without using the lafadz "al-yaum". The type of isti'arah in the verse describing the Day of Judgment is based on the mention of two main elements, including isti'arah makniyah (explicit metaphor) and isti'arah tashrihiyah (implicit metaphor). In addition, the type of isti'arah seen from the words used, includes isti'arah taba'iyah and isti'arah ashliyah. The meaning of the verse explains the condition of the disbelievers and believers, the recompense for their actions, hell and its inhabitants, as well as the phenomena that will occur on the Day of Judgment. The dominant uslub found is the type of Isti'arah Tamtsiliyyah/simile epic with the theme of hell and its inhabitants. Keywords: judgment day, isti'arah, Tafsir al-Munir, maknawi, lafdhi Abstrak: Ayat yang menggambarkan hari kiamat banyak menggunakan gaya bahasa perbandingan, salah satunya dengan uslub isti’arah (gaya bahasa metafora). Penelitian ini bertujuan untuk menemukan ayat penggambaran hari kiamat dengan uslub isti’arah di dalam Alquran. Penelitian dilakukan dengan menganalisis unsur-unsur, jenis, dan makna uslub isti’arah dalam ayat tersebut. Penelitian ini berupa deskriptif kualitatif dengan metode analisis makna dan kajian kepustakaan. Tafsir Al-Munir dijadikan sebagai rujukan utama dalam menentukan makna. Hasil penelitian menunjukkan ada 144 ayat dengan dua pola yaitu 97 ayat menyebutkan nama lain hari kiamat sesuai kejadiannya dengan menggunakan kata “al-yaum” dan 47 ayat menggambarkan hari kiamat secara umum/tanpa menggunakan lafadz “al-yaum”. Jenis isti’arah dalam ayat penggambaran hari kiamat berdasarkan penyebutan dua unsur pokoknya, mencakup isti’arah makniyah (metafora eksplisit) dan isti’arah tashrihiyah (metafora implisit). Selain itu, jenis isti’arah dilihat dari kata yang digunakan, mencakup isti’arah taba’iyah dan isti’arah ashliyah. Makna dari ayat-ayat tersebut menjelaskan keadaan orang kafir dan orang mukmin, balasan atas perbuatannya, neraka dan penghuninya, serta fenomena yang terjadi di hari kiamat. Gaya bahasa yang dominan ditemukan merupakan jenis Isti’arah Tamtsiliyyah/simile epos dengan tema neraka dan penghuninya. Kata Kunci: hari kiamat, isti’arah, tafsir al-Munir, jenis, makna